Using Conditional Value at Risk (CVaR) to select radiata pine trees for operational deployment - Pinto, Antonio A; Alzamora, Rosa M; Apiolaza, Luis A (Bosque (Valdivia), 2017)
Conditional Value at Risk (CVaR) was used to account for risk when building a portfolio of Pinus radiata trees for operational plantation deployment, under hypothetical changes on volume, modulus of elasticity, resin defects and lumber prices. The study considers three groups of trees grown to produce appearance lumber, structural lumber, or both. The CVaR model selected structural trees, which had high and variable returns across a wide range of risks, especially under low aversion scenarios; however, as risk-aversion increased, the model diversified incorporating trees producing both structural and appearance grades. Similarly, trees producing solely appearance grades, characterized by having the lowest returns variability, were only incorporated in scenarios of high risk-aversion.